A switch region inversion contributes to the aberrant rearrangement of a mu immunoglobulin heavy chain gene in MPC-11 cells. - Greenberg, R (1982)
We describe the unique features of an aberrantly rearranged mu immunoglobulin heavy chain gene isolated from MPC-11 cells (a gamma 2b producing Balb/c plasmacytoma). A novel rearrangement has occurred 1.5 Kb 5' of the MPC-11 mu gene (denoted 18b mu) resulting in the deletion of the majority of the repetitive switch region (S mu) and 5' flanking DNA including the Joining (JH) sequences. The remainder (275 bp) of the S mu repeat has undergone a complete sequence inversion. DNA sequences 5' of the inverted S mu sequence do not resemble Variable (VH), Diversity (D), JH or their conserved flanking sequences. A DNA sequence localized 5' of the inverted S mu sequence, (p18b mu-1.4) detects a small family of homologous sequences in Balb/c DNA. The 18b mu-1.4 like sequences lack homology to S mu, exhibit flanking sequence polymorphisms in 5 out of 6 inbred mouse strains and undergo partial or complete deletion in 5 out of 10 plasmacytomas tested. Two 18b mu-1.4 homologous sequences display a higher copy number in C57Bl/6, AL/N and CAL9 mouse strains.